Effects of source and level of added chromium on growth performance and carcass characteristics of growing-finishing pigs - P R O'Quinn; J W Smith II; K Q Owen; S A Blum; Jim L Nelssen; Michael D Tokach; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1998)
A growth trial \vas conducted to evaluate the effects of added chrOlniu111 nicotinate (CrNic) on growth performance and carcass composition of growing-finishing pi.gs (80 to 230 lb) and to compare 200 ppb of CrNic and chromium picolinate (CrPic). Few statistical responses were observed for growth performance, carcass characteristics, or serum chemistry profiles. These data suggest no beneficial responses to supplemental chromium in diets for growing-finishing barrows and gilts.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Growing-finishing pigs; Chromium nicotinate; Growth; Carcass quality